The Library Visit Study: user experiences at the virtual reference desk - Nilsen Kirsti (Information Research: An International Electronic Journal)
This paper discusses the methodology and reports on initial findings of a study examining the perceptions of users of digital reference services. It is part of a long-term research project, The Library Visit Study, which has been conducted in three phases at the University of Western Ontario for more than a decade. Phases One and Two examined perceptions of users who approached physical reference desks in libraries with reference questions. Phase Three of the research considers reference encounters at virtual reference desks and compares users' experiences at the physical reference desk with experiences at the virtual reference desk. The findings suggest that, from the viewpoint of the enquirer, the virtual reference desk suffers from the same problems as the physical reference desk: inadequate reference interviewing, referral to alternative sources without a subsequent check on their suitability, and a lack of follow-up to determine satisfaction in general.